2023
DOI: 10.18332/tid/168435
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness, prevalence, and regulations for the sale of electronic cigarettes in Arab countries: A narrative review

Feras Jirjees,
Yahya H. Dallal Bashi,
Zelal Kharaba
et al.

Abstract: The majority of the Arab countries have high records of daily tobacco smoking. Electronic cigarettes (e-cigarettes) use has exponentially increased in the past decade in Arab countries. Consumers' willingness to quit smoking traditional cigarettes and their perception of e-cigarettes as a safer alternative to conventional cigarettes have increased the demand for these devices. This narrative review aimed to gather and discuss the available literature on the awareness, prevalence, and sales regulations of e-cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Although this study did not account for the dual use of tobacco products, the results showed a pattern of several tobacco products used among students, among them e-cigarettes. Using combustible tobacco along with other products, such as e-cigarettes, is common among youth (21,22). Dual use of tobacco products is associated with higher odds of cardiovascular diseases and respiratory illness compared to the use of one tobacco product (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not account for the dual use of tobacco products, the results showed a pattern of several tobacco products used among students, among them e-cigarettes. Using combustible tobacco along with other products, such as e-cigarettes, is common among youth (21,22). Dual use of tobacco products is associated with higher odds of cardiovascular diseases and respiratory illness compared to the use of one tobacco product (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%